2008
DOI: 10.1002/ajmg.a.32429
|View full text |Cite
|
Sign up to set email alerts
|

An epidermal nevus syndrome with cerebral involvement caused by a mosaic FGFR3 mutation

Abstract: A 5-year-old Mexican girl had a bilateral, systematized epidermal nevus of a non-epidermolytic, non-organoid type covering large parts of her body with the exception of the scalp. Clinically, this nevus was of a soft, velvety type showing affinity to the large body folds. Histopathological examination revealed orthohyperkeratosis and papillomatosis without granular degeneration and without any abnormality of adnexal structures. During infancy she developed seizures, and subsequently a delayed mental developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…A widespread mosaicism of the FGFR3 mutation was suggested in a 5-year-old girl with a mosaic phenotype of ENS. [15] A case of discordant monozygotic (MZ) twins with severe ENS, supporting the concept of a postzygotic mutation, is on record. [16] Henceforth, activating FGFR3 mutations in the human epidermis, secondary to a postzygotic mutation in early embryonic development, may be the key event in the pathogenesis of ENS and needs further exploration.…”
Section: Discussionmentioning
confidence: 98%
“…A widespread mosaicism of the FGFR3 mutation was suggested in a 5-year-old girl with a mosaic phenotype of ENS. [15] A case of discordant monozygotic (MZ) twins with severe ENS, supporting the concept of a postzygotic mutation, is on record. [16] Henceforth, activating FGFR3 mutations in the human epidermis, secondary to a postzygotic mutation in early embryonic development, may be the key event in the pathogenesis of ENS and needs further exploration.…”
Section: Discussionmentioning
confidence: 98%
“…Somatic mosaicism for FGFR3 mutations involving skin and other organ systems have been described in patients. [89] If the mutation involves the gonads, such patients are said to be at risk for thanatophoric dysplasia. [9] In many other patients with epidermal nevi, somatic mutations resulting in mosaicism confined to keratinocytes of the affected area have been demonstrated in the FGFR3 gene,[10] specifically at the R248C hotspot, and in the PIK3CA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Hernandez et al reported several patients with multiple EN with the same FGFR3 R248C mutation, but without the severe achondroplastic phenotype that is usually associated with R248C germline mutations 18. Of even greater interest, an undoubted mosaic FGFR3 mutation has been reported in a patient showing multiple EN, seizures and mental retardation 6. The higher risk of cancer conferred by mosaic mutations in FGFR3 or PIK3CA is all the more plausible since several cases of young patients harbouring both EN and low-grade bladder cancers have been reported (case report and review by Garcia de Jalon et al 19).…”
Section: Discussionmentioning
confidence: 99%
“…EN can occasionally be associated with complex developmental abnormalities in so called epidermal nevus syndromes 6. It is also seen in the Proteus syndrome which is related to deleterious PTEN mutations that enhance the PIK3CA activity 7 8.…”
mentioning
confidence: 99%